Mutation Screening of the CYP1B1 Gene Reveals Novel and Recurrent Pathogenic Variants in Pakistani Primary Congenital Glaucoma Patients - Waqas Ali Surhio; Feriha Fatima Khidri; Mohsin Iqbal Haroon; Samia Mehmood; Yar Muhammad Waryah (JLUMHS)
OBJECTIVE: To identify the pathogenic alleles in primary congenital glaucoma patients for early cure of the disease METHODOLOGY:  A cross-sectional descriptive study was carried out after approval from the ethical committee of SIOVS from December 2022 to November 2023 at Sindh Institute of Ophthalmology & Visual Sciences, Hyderabad. The consanguineous pedigree consisting of more than one affected was included, and the pedigree consists only one affected or secondary cause of vision loss was excluded. After getting informed consent, ten cc blood samples from all available participants in the pedigree were drawn, and DNA was extracted. The ARMS Assay and Sanger sequencing methods were adapted to analyze the CYP1B1 gen. RESULTS: In the present study, one novel c.1187C>T, p.Pro396Leu and one reported c.1169G>A, p.Arg390His allele in CYP1B1 gene were found in two isolated pedigrees enrolled from Sindh Pakistan. ARMS Assay method and the Sanger sequencing method were adopted to detect pathogenic variants. Bioinformatics tools were used to analyze the pathogenesis of identified alleles and compare phenotype-genotype correlation. CONCLUSION:  The findings of novel and frequently reported mutations have a significant role in advancing genetic testing protocols, enabling more accurate targeting of diagnoses and identified alleles that may be added to existing repositories of the genetic database